Pengaruh Penerapan Standar Akuntansi Pemerintah, Pengawasan dan Kualitas Aparatur Pemerintah Daerah Terhadap Kualitas Laporan Keuangan(Studi Kasus Pada Pemerintah Kabupaten Pati Tahun 2014) - Nugroho, Hari Raditya (2016)
Good financial statement of local government and also center have to with quality, where made to present the relevant information, andal and reliably with reference to financial position and entire transaction data noted by an entitas reporting of during one reporting period which every year. This research was aim to analyse the application of government's accounting standardization, controlling, and quality of local government aparatur toward the quality of the financial statement Pati Sub Province. This research was representing the quantitative research, by the data source in the form of primary data obtained from questioner. Sum up the sample research counted 54 responders taken by purposive sampling. Analyzer used cover data quality test, classic assumption test, multiple linear regressions analyze and hypothesis test covering F test, coefficient determinasi R2 test, and t test. The results of analysis can be conclusion that the application of government's accounting standardization have an significant effect toward the quality of the financial statement Pati Sub Province, was proven from t count value equal to 3,909 > t table (2,009), controlling statement have an significant effect toward the quality of the financial statement Pati Sub Province, was proven from t count value equal to 3,359 > t table (2,009), and quality of local government aparatur have an significant effect toward the quality of the financial statement Pati Sub Province, was proven from t count value equal to 6,054 > t table (2,009). So that hypothesis from H1 until H3 was truth acceptable.